Association of plasma Fetuin-A and clinical characteristics in patients with new-onset type 2 diabetes mellitus - Yin, Liang (Int J Clin Exp Med, 2015)
Context: Fetuin-A is an abundant plasma protein known to inhibit insulin signaling and pathologic calcification, has emerged as a promising candidate biomarker for diabetes risk. Objective: The objective of this study was to investigate the relationships between plasma Fetuin-A level with clinical characteristics in patients with new-onset type 2 diabetes mellitus (nT2DM). Subjects and Methods: Plasma Fetuin-A levels, and clinical characteristics were assessed in 100 patients with nT2DM and 100 normal glucose tolerance (NGT). Results: nT2DM subjects had significantly higher Fetuin-A levels than NGT subjects (368.5 ± 15.6 vs 152.7 ± 7.1 mg/ml, P < 0.01). In the Pearson’s correlation coefficients, Fetuin-A levels and clinical parameters. Fetuin-A was positively correlated with HOMA-insulin resistance index (HOMA-IR), carotid intima media thickness(CIMT), HbA1c, triglyceride (TG), Low-density lipoprotein cholesterol (LDL-C), body mass index (BMI), systolic blood pressure (SBP), fasting plasma glucose (FBG) and 2 h post-glucose load blood glucose (2 h OGTT) (P < 0.05 and P < 0.01), but negatively with fasting plasma insulin (FINS), 2 h plasma insulin after glucose overload (PINS), High-density lipoprotein cholesterol (HDL-C) and HOMA-beta-cell insulin secretion index (HOMA-IS) (P < 0.05 and P < 0.01). However, no significant relationships were observed between plasma Fetuin-A levels and estimated glomerular filtration rate (eGFR), age and gender in nT2DM subjects. In a multiple linear regression analysis, Fetuin-A levels were independently associated with FBG, 2 h OGTT, HOMA-IS, TG, and CIMT (R(2) = 0.6760). CIMT were negatively associated with FINS and HDL-C (r = -0.33, P = 0.008; r = -0.31, P = 0.01, respectively) in the Pearson’s analyses. Moreover, they were positively associated with HOMA-IR (r = 0.28, P = 0.03). It showed significant correlations of plasma CIMT with FINS, PINS and HOMA-IR (R(2) = 0.6760). Conclusions: Our study suggests that the plasma Fetuin-A levels may be associated with macroangiopathies in nT2DM patients. Therefore, detecting early plasma Fetuin-A levels nT2DM provides an opportunity to intervene of carotid artery disease in diabetic patients and giving timely treatment for the prevention of diabetic vascular complications.